On fitness: how do mutations shape the biology of cancer?. (8th March 2019) - Majewski, Ian J.
Abstract : The theory of evolution by natural selection shapes our understanding of the living world. While natural selection has given rise to all the intricacies of life on the planet, those responsible for treating cancer have a darker view of adaptation and selection. Revolutionary changes in DNA sequencing technology have allowed us to survey the complexities that constitute the cancer genome, while advances in genetic engineering are allowing us to functionally interrogate these alterations. These approaches are providing new insights into how mutations influence cancer biology. It is possible that with time, this new knowledge will allow us to take control of the evolutionary processes that shape the disease, to develop more effective treatments.